Inhibitory effects of cashew Anacardium occidentale L. kernel, apple, and shell extracts on lipid accumulation and adipogenesis in 3T3-L1 adipocytes - Munkhzul Ganbold; Shinya Takahashi; Osamu Kakui; Mitsutoshi Nakajima; Hiroko Isoda (Scientific Reports)
Abstract Obesity, a major risk factor for various metabolic diseases, often results in dysfunctional white adipose tissue and altered adipogenesis leading to ectopic fat accumulation, inflammation, and insulin resistance. On the other hand, cashew (Anacardium occidentale L.) nut worldwide consumption and production is increasing steadily, which augments the mass of byproducts to be discarded. Indeed, cashew apples and cashew shells have shown potent effects to lower adiposity weight in human and animal models. However, the direct effect on adipocyte differentiation still remains unexplored. Therefore, this study aimed to investigate the biological effect of cashew nut or kernel (CK), dried cashew apple (DA), and cashew shell (SH) ethanolic extracts on 3T3-L1 adipocyte differentiation and lipid accumulation. SH showed strong inhibition on adipocyte differentiation by downregulating transcription factors, PPARγ, C/EBPα, and SREBP-1. DA also inhibited the transcription factors accompanied by reduced lipid accumulation, while proteins for de novo lipogenesis were unchanged. Finally, CK did not alter any markers in adipocyte differentiation, however, interestingly adiponectin level was significantly increased. Concisely, our findings showed that CK ameliorates adiponectin production without interfering adipogenesis, while DA lowers lipid accumulation and SH suppresses adipogenesis.